Kampanye Lingkungan Hidup Forum Komunitas Hijau dalam Pelestarian Alam di Kota Banjarmasin: Kampanye Lingkungan Hidup Forum Komunitas Hijau dalam Pelestarian Alam di Kota Banjarmasin - Hanief, Lalita; Sari, Noviana; Sanjaya, Andika (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Waste management and greening are noteworthy problems in Banjarmasin river city. The purpose of this study was to determine the implementation of “Forum Komunitas Hijau” (FKH) Environmental Campaign in Nature Conservation in Banjarmasin City. This research uses a descriptive qualitative approach. Data collection techniques using semi-structured interviews, documentation, library research, with data analysis techniques such as CAQDAS. The results showed that the FKH environmental campaign took the form of problem analysis, audience analysis, assigning media, selecting media, developing messages, producing media, implementing programs, monitoring, and evaluating. They use banners, shirts, and facebook groups, using Indonesian and Banjar languages.